(untitled) (Community Based Medical Journal, 2026)
Medical termination of intrauterine feat demise (IUFD) seeks effective uterine evacuation with minimal complications. Since misoprostol alone is commonly used, mifepristone pretreatment may improve efficacy; however, comparative evidence in Bangladesh is very limited. A cross-sectional, comparative study was conducted in the Department of Obstetrics & Gynaecology of Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and December of 2023, to compare the efficacy and safety of combined mifepristone and misoprostol therapy with misoprostol alone for medical termination of IUFD. A total of 80 women with confirmed IUFD were purposively allocated in two groups having 40 in each group – group A received mifepristone followed by misoprostol, while group B received only misoprostol. Primary outcomes were induction-to-expulsion interval and complete expulsion rate; while secondary outcomes included total misoprostol dose and maternal complications. The induction-to-expulsion interval was much lower in group A compared to group B (14.2±3.6 hours vs. 22.8±5.1 hours; p<0.001). Regarding treatment success, complete expulsion within 24 hours was achieved much more in group A compared to group B (92.5% vs. 72.5%; p<0.05). The total dose of misoprostol required was significantly lower in group A as doses of ≤600 µg were sufficient in 65.0% of women receiving mifepristone pretreatment, whereas 62.5% of women in the misoprostol alone group (group B) required ≥800 µg (p<0.05). Adverse effects such as fever, nausea/vomiting and excessive bleeding were observed in both groups. However, the overall incidence of adverse effects was comparable and no statistically significant differences were observed (p>0.05). Combined therapy with mifepristone and misoprostol are more effective than using only misoprostol for termination of IUFD offering shorter induction time and higher success rate without increasing maternal risk. CBMJ 2026 July: Vol. 15 No. 02 P:150-155